Architecture of the Pol III–clamp–exonuclease complex reveals key roles of the exonuclease subunit in processive DNA synthesis and repair. (2nd April 2013) - Toste Rêgo, Ana; Holding, Andrew N; Kent, Helen; Lamers, Meindert H
<x xml:space="preserve">Abstract</x> DNA polymerase III (Pol III) is the catalytic α subunit of the bacterial DNA Polymerase III holoenzyme. To reach maximum activity, Pol III binds to the DNA sliding clamp β and the exonuclease ε that provide processivity and proofreading, respectively. Here, we characterize the architecture of the Pol III–clamp–exonuclease complex by chemical crosslinking combined with mass spectrometry and biochemical methods, providing the first structural view of the trimeric complex. Our analysis reveals that the exonuclease is sandwiched between the polymerase and clamp and enhances the binding between the two proteins by providing a second, indirect, interaction between the polymerase and clamp. In addition, we show that the exonuclease binds the clamp via the canonical binding pocket and thus prevents binding of the translesion DNA polymerase IV to the clamp, providing a novel insight into the mechanism by which the replication machinery can switch between replication, proofreading, and translesion synthesis.